Sentidos atribuídos à qualidade de vida relacionada à saúde pelas cuidadoras de adolescentes com diabetes Mellitus tipo 1 - Pessoa, Marina Saraiva de Araújo (2022)
Introduction: Type 1 diabetes mellitus is a complex chronic disease, with a high rate in adolescents and that affects family functioning and the Health-Related Quality of Life of each member. Objectives: To interpret the meanings attributed to Health-Related Quality of Life by caregivers of adolescents with type 1 diabetes mellitus; and understand how changes in family functioning interfere with the perception of Health-Related Quality of Life, in the light of the Calgary Family Assessment Model. Methodology: Qualitative, descriptive-exploratory study, developed in the outpatient clinic of a referral hospital for the treatment of diabetes in the state of Paraíba, with 14 caregivers of adolescents with type 1 diabetes mellitus. Empirical data collection took place in person and remotely, in the period between May and September 2021, based on the manual construction of a genogram and ecomap, and a semi-structured interview. data were interpreted through inductive thematic analysis, in light of the concepts of Health-Related Quality of Life and family functioning. The research was approved by opinion nº 4.711.978 and CAAE: 43825021.7.0000.5188. Results: The meanings attributed to Health-Related Quality of Life by caregivers are correlated with the feeling of being healthy, healthy eating, satisfactory family income, family involvement in care and access to an effective care network. Type 1 diabetes mellitus negatively interfered with family functioning, especially in the period after diagnosis and, more intensely, in families with preexisting family conflicts and without a social support network. Final Considerations: With the study, it was possible to apprehend the meanings that the caregivers attributed to their Health-Related Quality of Life and family functioning. Knowing these aspects can help health professionals who work in the management of care to be able to intervene on time in the demands of the family and the adolescent with this comorbidity.